qk ?Laplace Transform on Quantum Integral - Yılmazer, Mehmet Çağrı; Göktaş, Sertac; Yılmaz, Emrah; Et, Mikail (Association of Mathematicians (MATDER), 2024)
In this study, we present qk ?Laplace transform by qk ?integral on quantum analogue. We give some properties of qk ?Laplace transform. The qk ?Laplace transforms of some common functions are calculated. © MatDer.
Keywords: Laplace transformation; qk ?calculus; q?calculus